2018
DOI: 10.1016/j.ica.2017.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of trichlorosalicylic acid with alkaline and first row transition metals as a switch for their antibacterial activity

Abstract: CitationKumar V, Chawla M, Cavallo L, Basit Wani A, Manhas A, et al. (2017) Complexation of trichlorosalicylic acids by alkaline and first row transition metals as a switch for their antibacterial activity. Inorganica Chimica Acta. Available: http:// dx.NirajUpadhyay, Complexation of trichlorosalicylic acids by alkaline and first row transition metals as a switch for their antibacterial activity, Inorganica Chimica Acta (2017), doi: http://dx. Abstract:3,5,6-trichlorosalicylic acid (TCSA) does not show a goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Since the medicines form various plants have significant influence on protein-binding properties. The interesting point of the study is that extract under study has shown least binding rate with BSA protein as compared to acetylsalicylic acid, which is the feature of good medicines [21,22]. However, complexation with albumin proteins can stabilize the medicines against aggregation, leading to retention of the antimicrobial activities .…”
Section: Anti-inflammatory and Protein Binding Assaymentioning
confidence: 96%
See 1 more Smart Citation
“…Since the medicines form various plants have significant influence on protein-binding properties. The interesting point of the study is that extract under study has shown least binding rate with BSA protein as compared to acetylsalicylic acid, which is the feature of good medicines [21,22]. However, complexation with albumin proteins can stabilize the medicines against aggregation, leading to retention of the antimicrobial activities .…”
Section: Anti-inflammatory and Protein Binding Assaymentioning
confidence: 96%
“…Quantitative analysis of TFC and TPC was analyzed as per the protocols explained in literature [11][12][13][14][15][16][17]. Protein binding and binding constant calculations of drugs under the study were performed by well-described methods in literature [18][19][20][21][22]. Anti-inflammatory assay was performed by following the bovine serum albumin (BSA) protein method [9][10][11].…”
Section: Antioxidant Total Phenolic Content (Tpc) Total Flavonoids Content (Tfc) Anti-inflammatory and Protein Binding Assays Using Uv-vimentioning
confidence: 99%
“…In spectroscopic analysis, very good agreement between computational and experimental data was observed. The negotiable differences were observed because theoretical calculations were performed in the gaseous phase, while the experimental results were obtained in the solid/liquid phase [32][33][34][35][36][37][38]. Excellent results were obtained for UV-visible analysis, where negligible difference was observed between the computational and experimental analysis.…”
Section: Experimental Cum Computational Comparative Spectroscopic Anamentioning
confidence: 99%
“…The higher difference (>20 cm −1 ) was observed at the N-H frequencies of molecules 3. It was due to the involvement of N-H in resonance with C9O [34][35][36][37]. There was less than 20 cm −1 difference observed in the P-O frequency molecule 4.…”
Section: Experimental Cum Computational Comparative Spectroscopic Anamentioning
confidence: 99%
See 1 more Smart Citation